FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK KENDARAAN BERMOTOR DI KOTA TANGERANG - Natasha Olivia; Mohammad Eddy Rosyadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research is to obtain empirical evidence related to the effect of the number of motor vehicles, input mutations, output mutations, taxpayer compliance, vehicles not re-registering, and government policies on Motor Vehicle Tax revenue in Tangerang City. The research data was obtained from the Monthly Report of Realisasi PAD managed by BPD Provinsi Banten UPT Bapenda Cikokol and Ciledug per month and Banten Governor Regulation during 2018 to 2022. Purposive sampling method was used in research sampling with total 116 data after outliers. The hypothesis test used is a multiple regression model. The results of this research show that the number of motor vehicles, output mutations, and taxpayer compliance affect motor vehicle tax revenue. Three other independent variables, namely input mutation, vehicle not re-registering, and government policy have no influence on motor vehicle tax revenue.